A faunistic study of the South African Aphididae, excluding the subfamily Aphidinae (Hemiptera: Aphidoidea) - Millar, I. M (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) - University of Stellenbosch, 1986.